The 9aaTAD Transactivation Domains: From Gal4 to p53. - Martin Piskacek (PLoS ONE, 2016)
The family of the Nine amino acid Transactivation Domain, 9aaTAD family, comprises currently over 40 members. The 9aaTAD domains are universally recognized by the transcriptional machinery from yeast to man. We had identified the 9aaTAD domains in the p53, Msn2, Pdr1 and B42 activators by our prediction algorithm. In this study, their competence to activate transcription as small peptides was proven. Not surprisingly, we elicited immense 9aaTAD divergence in hundreds of identified orthologs and numerous examples of the 9aaTAD species' convergence. We found unforeseen similarity of the mammalian p53 with yeast Gal4 9aaTAD domains. Furthermore, we identified artificial 9aaTAD domains generated accidentally by others. From an evolutionary perspective, the observed easiness to generate 9aaTAD transactivation domains indicates the natural advantage for spontaneous generation of transcription factors from DNA binding precursors.